Treatment of benzodiazepine withdrawal syndrome in a severe traumatic brain injury patient - Teah, M.K.; Chan, G.K.; Wong, M.T.F.; Yeap Boon Tat (BMJ Publishing Group, 2021)
Prolonged exposure to benzodiazepines (BDZ) may contribute towards physical dependence, which is manifested by iatrogenic Benzodiazepine Withdrawal Syndrome (BWS), a condition often underdiagnosed. Current evidence recommends precluding BDZ infusion as sedation in the intensive care unit to avoid possible withdrawal and delirium issues. Administration of dexmedetomidine should be considered to facilitate weaning in patients with BWS. © 2021 BMJ Publishing Group. All rights reserved.